2008
DOI: 10.4049/jimmunol.181.4.2764
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytes Support Oval Cell-Dependent Liver Regeneration

Abstract: In case of hepatic damage, the liver uses a unique regeneration mechanism through proliferation of hepatocytes. If this process is inhibited, bipotent oval stem cells proliferate and differentiate to hepatocytes and bile ducts, thus restoring liver mass. Although oval cell accumulation in the liver is often associated with inflammatory processes, the role of lymphocytes in oval cell-mediated hepatic regeneration is poorly understood. We treated wild-type and immunodeficient mice with an oval cell-inducing diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 51 publications
4
52
1
1
Order By: Relevance
“…As previous studies have suggested that nonepithelial populations such as mesenchymal cells and immune cells reside near and around LPCs (Paku et al 2001;Knight et al 2007;Strick-Marchand et al 2008), we suspected that those cells may functionally interact with LPCs and provide a putative LPC niche. To identify and characterize such an LPC-niche interaction, we first induced the LPC response in the mouse liver with a well-established protocol of the hepatotoxin DDC diet application (Preisegger et al 1999).…”
Section: Thy1mentioning
confidence: 99%
“…As previous studies have suggested that nonepithelial populations such as mesenchymal cells and immune cells reside near and around LPCs (Paku et al 2001;Knight et al 2007;Strick-Marchand et al 2008), we suspected that those cells may functionally interact with LPCs and provide a putative LPC niche. To identify and characterize such an LPC-niche interaction, we first induced the LPC response in the mouse liver with a well-established protocol of the hepatotoxin DDC diet application (Preisegger et al 1999).…”
Section: Thy1mentioning
confidence: 99%
“…Oval cells are derived from the canal of Hering, and in rodents this canal barely extends beyond the limiting plate ( Figures 4, 5); in contrast, in human liver the organization of the biliary tree is different, with the canal of Hering extending to the proximate third of the lobule [68] and so apparently requiring a name change from oval cells to 'hepatic progenitor cells' (HPCs) [69]. An enormous range of markers has been used to identify ovals cells (Table 2) [70][71][72][73][74][75][76][77][78][79][80][81][82][83] and some, such as Dlk, may signal imminent hepatocyte differentiation [71]. A popular experimental procedure to elicit an oval cell response in rats is to pre-treat the animals with 2-acetylaminofluorene (2-AAF) before performing a two-thirds PH (the 2-AAF/PH protocol).…”
Section: The Facultative Stem Cell Response: Oval/hepatic Progenitor mentioning
confidence: 99%
“…Hedgehog (Hh) signalling acting through the receptor Patched (PTC) on oval cells/HPCs is required for their survival [76]. Perhaps most significantly, inflammatory cells produce a range of cytokines and chemokines that initiate the response [82,83]; SDF-1 attracts CXCR4 + T cells, and these cells express TNF-like weak inducer of apoptosis (TWEAK), which stimulates oval cell proliferation by engaging its receptor Fn14 [80]. Other elements of the inflammatory response that may stimulate oval cells include lymphotoxin-β, IFNγ , TNFα and even histamine [81].…”
Section: The Facultative Stem Cell Response: Oval/hepatic Progenitor mentioning
confidence: 99%
“…Peripheral immune cells such as T-cells are required during adulthood for the regulation of proliferation and differentiation of certain stem cells, as demonstrated for the regeneration of hepatocytes from liver stem cells after liver damage (Strick-Marchand et al, 2008). Similarly, T-lymphocytes and microglia are required for the activitydependent modulation of hippocampal neurogenesis and spatial learning abilities in adulthood (Ziv et al, 2006).…”
Section: Antiinflammatory Treatment Blocks the Proliferation And Actimentioning
confidence: 99%